2011
DOI: 10.1007/s12149-011-0529-4
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of FDG-PET to contrast enhanced-computed tomography (CT) for the diagnosis of mediastinal lymph node metastasis in non-small cell lung cancer: a Japanese multicenter clinical study

Abstract: The addition of FDG-PET to contrast-enhanced CT imaging for the staging of NSCLC improved the diagnostic accuracy for mediastinal lymph node metastasis. FDG-PET improved the precision of the staging of NSCLC and contributed to the surgical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Interestingly, we found concurrent lung disease or diabetics and non-adenocarcinoma were also risk factors for occult nodal metastasis, although Kubota [18] insisted on that the accuracy of PET/CT were not affected as long as the blood glucose level in diabetic patients was controlled at less than 140mg/dL and Kanzaki [19] thought occult lymph node metastasis more likely to occur in patients of lung adenocarcinoma. Obviously, it showed a distinct trend in this study that there are five diabetic patients of 17 false negative cases.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, we found concurrent lung disease or diabetics and non-adenocarcinoma were also risk factors for occult nodal metastasis, although Kubota [18] insisted on that the accuracy of PET/CT were not affected as long as the blood glucose level in diabetic patients was controlled at less than 140mg/dL and Kanzaki [19] thought occult lymph node metastasis more likely to occur in patients of lung adenocarcinoma. Obviously, it showed a distinct trend in this study that there are five diabetic patients of 17 false negative cases.…”
Section: Discussionmentioning
confidence: 83%
“…PET scanning is highly sensitive for the detection of mediastinal metastasis [18]. A controlled multicenter clinical study reported that FDG-PET improved diagnosis precision for mediastinal lymph nodes [19]. One of the limitations of the present study was that PET-scanning was initiated in 2004, and not all cases were examined using this method.…”
Section: Discussionmentioning
confidence: 95%
“…A similarly designed, larger study from Belgium confirmed the superiority of 18 F-FDG-PET added to CT in the accurate staging of N2/N3 metastasis (Vansteenkiste et al, 1998). Pieterman et al (2000) reported a sensitivity and specificity of 91 and 86% for 18 F-FDG-PET compared with 75 and 66% for CT. A multicenter prospective investigation from Japan similarly demonstrated a statistically significant improvement in the accuracy and specificity of integrated 18 F-FDG-PET/CT with a modern hybrid scanner over standard CT alone in the evaluation of mediastinal lymph nodes (Kubota et al, 2011). A summary of the studies that have evaluated the performance of 18 F-FDG-PET and 18 F-FDG-PET/CT in evaluating the mediastinum is shown in Table 1 .…”
Section: Staging Of the Mediastinummentioning
confidence: 99%